2021
DOI: 10.3390/antiox10091411
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid Nanofibers Attenuated Particulate Matter-Induced Oxidative Stress in Keratinocytes

Abstract: Airborne particulate matter (PM) is one of the indicators of air pollution, and it is also the main factor causing oxidative stress in the skin. Oleanolic acid (OA), a natural terpenoid compound, effectively inhibited PM-induced skin aging; however, OA has poor water solubility and skin absorption, which limit its application in medicines and cosmetics. The aim of this study was to prepare oleanolic acid nanofibers (OAnf) and evaluate the effects of OA and OAnf in PM-treated keratinocytes. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In Alzheimer's disease, oleanolic acid regulates UCP2 expression via STC-1 to attenuate oxidative stress and β-amyloid levels in N2a/APP695swe cells [ 9 ]. It has also been shown that skin damage caused by airborne PM2.5 particles can be alleviated by the antioxidant effect of oleanolic acid [ 10 ]. In hypertension, hypertension promotes endoplasmic reticulum stress and ROS accumulation in kidney cells, while oleanolic acid inhibits the progression of hypertensive nephropathy by reducing ROS levels [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease, oleanolic acid regulates UCP2 expression via STC-1 to attenuate oxidative stress and β-amyloid levels in N2a/APP695swe cells [ 9 ]. It has also been shown that skin damage caused by airborne PM2.5 particles can be alleviated by the antioxidant effect of oleanolic acid [ 10 ]. In hypertension, hypertension promotes endoplasmic reticulum stress and ROS accumulation in kidney cells, while oleanolic acid inhibits the progression of hypertensive nephropathy by reducing ROS levels [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug loading was 98.19 ± 4.82%, and the encapsulation efficiency was greater than 99%. OAnf significantly improved water solubility (998.7 ± 58.32 µg/mL) and skin penetration (45.27 µg/cm 2 ) at 4 h compared to OA alone [ 179 ].…”
Section: Challenges In Oa Deliverymentioning
confidence: 99%